Average Error: 0.0 → 0.0
Time: 9.8s
Precision: 64
$\left(1 - \lambda\right) \cdot pa + \lambda \cdot pb$
$\left(1 - \lambda\right) \cdot pa + \lambda \cdot pb$
\left(1 - \lambda\right) \cdot pa + \lambda \cdot pb
\left(1 - \lambda\right) \cdot pa + \lambda \cdot pb
double f(double lambda, double pa, double pb) {
double r2166519 = 1.0;
double r2166520 = lambda;
double r2166521 = r2166519 - r2166520;
double r2166522 = pa;
double r2166523 = r2166521 * r2166522;
double r2166524 = pb;
double r2166525 = r2166520 * r2166524;
double r2166526 = r2166523 + r2166525;
return r2166526;
}


double f(double lambda, double pa, double pb) {
double r2166527 = 1.0;
double r2166528 = lambda;
double r2166529 = r2166527 - r2166528;
double r2166530 = pa;
double r2166531 = r2166529 * r2166530;
double r2166532 = pb;
double r2166533 = r2166528 * r2166532;
double r2166534 = r2166531 + r2166533;
return r2166534;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(1 - \lambda\right) \cdot pa + \lambda \cdot pb$
2. Final simplification0.0

$\leadsto \left(1 - \lambda\right) \cdot pa + \lambda \cdot pb$

# Reproduce

herbie shell --seed 1
(FPCore (lambda pa pb)
:name "((1.0 - lambda) * pa) + (lambda * pb)"
:precision binary64
(+ (* (- 1 lambda) pa) (* lambda pb)))